Assessments of 15 Exploited Fish Stocks in Chinese, South Korean and Japanese Waters Using the CMSY and BSM Methods - Liang, Cui; Xian, Weiwei; Pauly, Daniel (Frontiers in Marine Science, 2020)
The status of fifteen marine fish and invertebrate populations exploited by Chinese, South Korean or Japanese fishing fleets were assessed, using two newly developed computer-intensive methods, CMSY and BSM. The results show that among these fifteen populations in question, 2 have collapsed, 3 are grossly over-fished and 9 are overfished. Also, we compared results of the CMSY and BSM methods, and it shows that, while the CPUE data for use with the BSM method lead to narrower confidence intervals and may modify the shape of the biomass trajectory, they do not lead to over- or underestimates of terminal B/BMSY values. These results, although still tentative because the methods used to generate them are relatively new, generally match what is known of the status and exploitation of the populations in question, which makes CMSY and BSM to be promising stock assessment approaches in data-sparse situations. Based on our results, a consistent signal is obtained, thus suggesting that a reduction in fishing pressure would be necessary to restore the abundance status of these fifteen populations.